Cross-border spread of a mosaic resistance (OXA-48) and virulence (aerobactin) plasmid in Klebsiella pneumoniae: a European Antimicrobial Resistance Genes Surveillance Network investigation, Europe, February 2019 to October 2024 - Anke Kohlenberg (Eurosurveillance, 2025)
An investigation of the European Antimicrobial Resistance Genes Surveillance Network (EURGen-Net) detected the same mosaic IncHI1B(pNDM-MAR) resistance (OXA-48) and virulence (aerobactin) plasmid in 492 Klebsiella pneumoniae isolates from eight European Union countries during 2019–2024. Involvement of various K. pneumoniae sequence types (STs), multiple introductions, followed by large clonal outbreaks of three STs (ST147, ST392, ST45) carrying the plasmid in two countries indicate a high risk for further spread of this plasmid and a potential for difficult-to-treat K. pneumoniae infections to rise.